2008
DOI: 10.1007/s00128-008-9479-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of a Neonicotinoid Insecticide, Acetamiprid on Chili (Capsicum annum L.)

Abstract: An experiment was conducted to find out the persistence of two different formulations of Acetamiprid, namely 20% SP (soluble powder) and 20% SL (soluble liquid) in chili. Following three applications @ 20 g a.i./ha and 40 g a.i./ha, the initial deposits were found to be 0.0207, 0.0405, 0.0244 and 0.1039 microg/g. The half-life values of acetamiprid in chili were in the range of 2.24-4.84 days. A waiting period of 1 day is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 1 publication
0
20
1
Order By: Relevance
“…As a promising insecticide, acetamiprid is used for controlling Hemiptera (especially aphids), Thysanoptera, Lepidoptera, and so on . However, acetamiprid is inevitably released into the environment due to its extensive use, and its residues can be detected in a variety of plants . Therefore, long term and intensive use of pesticides may contaminate agricultural land and water, adversely affecting nontarget organisms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a promising insecticide, acetamiprid is used for controlling Hemiptera (especially aphids), Thysanoptera, Lepidoptera, and so on . However, acetamiprid is inevitably released into the environment due to its extensive use, and its residues can be detected in a variety of plants . Therefore, long term and intensive use of pesticides may contaminate agricultural land and water, adversely affecting nontarget organisms …”
Section: Introductionmentioning
confidence: 99%
“…3 However, acetamiprid is inevitably released into the environment due to its extensive use, and its residues can be detected in a variety of plants. [4][5][6] Therefore, long term and intensive use of pesticides may contaminate agricultural land and water, adversely affecting nontarget organisms. [7][8][9] The silkworm, Bombyx mori, is an important economic insect that belongs to the order of Lepidoptera.…”
Section: Introductionmentioning
confidence: 99%
“…Acetamiprid exposure has been proven to have adverse effect on greenhouse workers spraying acetamiprid [8], soil microorganisms [25] and beneficial insects [24]. In recent years, acetamiprid residues in crops are receiving considerable attention due to their potential toxicity to humans [9], [10], and methods for the biotransformation of neonicotinoids are being actively researched. Microbial degradation is considered as an efficient “green” solution to eliminate environmental polluting chemicals [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption and translocation of acetamiprid in various crops have been previously assessed by researchers. It was reported that acetamiprid dissipated by about 5–21 and 25–38% on day 1 after the application of the recommended dose (5 g a.i./100 L water) and double the recommended dose (10 g a.i./100 L water) in chilli (Sanyal et al ., 2008). The dissipation of acetamiprid residues increased with increasing time after application, reaching 60–69 and 78–89% on day 7, after the application of the recommended and double the recommended doses.…”
Section: Resultsmentioning
confidence: 99%
“…In the Republic of Korea, acetamiprid was registered and has been used since 2001 and its maximum residue limits were established for 32 foodstuffs (Korea Food and Drug Administration, 2010). It was reported that the half‐life value of acetamiprid was 11.1 days under UV light, 25.1 days under sunlight in soil (Gupta et al ., 2008), 1–2 days in field soils (Tokieda et al ., 1999; Hong et al ., 2001), 1.02–1.59 days in the mustard plant (Pramanik et al ., 2006), 1.82 to 2.33 days in tea (Gupta and Shanker, 2008) and 2.24 days in chilli (Sanyal et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%